Art and architecture of Ireland : Volume 2: Painting, 1600-1900 - Carpenter, Andrew; Carpenter, Andrew; Figgis, Nicola; Figgis, Nicola (Royal Irish Academy, 2015)
Connoisseurship and the art market -- Art institutions and training in Ireland and abroad -- Subjects and genres -- Cultural impact and influence -- Methods and materials -- Biographies -- Appendix Society of Artists of Ireland.